Analysis Of Effect Of Human Resources, Allocation Of Funds, Materials, and Construction Equipment On Performance Of Road Maintenance In Jepara Regency - Hanief Kurniawan (International Conference on Coastal and Delta Areas, 2017)
The availability of adequate facilities and road infrastructure is one indicator of community welfare. Jepara Regency Government through road maintenance program trying to keep the road condition to stay steady. Human resources, allocation of funds, materials, and construction equipment are the main factors determining road maintenance performance. This study aims to identify and analyze these factors so that it can be known the effect on road maintenance performance in Jepara regency. The results of the analysis conducted on the sample of respondents totaling 90 people showed that: 1) Human resources, allocation of funds, materials, and construction equipment respectively partially have a positive and significant impact on road maintenance performance; 2) Human resources, allocation of funds, materials, and construction equipment simultaneously have a positive and significant impact on road maintenance performance. Keywords: human resources, allocation of funds, materials, equipment, maintenance